Transcriptomes of Injured Lamprey Axon Tips: Single-Cell RNA-Seq Suggests Differential Involvement of MAPK Signaling Pathways in Axon Retraction and Regeneration after Spinal Cord Injury - Li-Qing Jin; Yan Zhou; Yue-Sheng Li; Guixin Zhang; Jianli Hu; Michael E. Selzer (Cells, 2022)
Axotomy in the CNS activates retrograde signals that can trigger regeneration or cell death. Whether these outcomes use different injury signals is not known. Local protein synthesis in axon tips plays an important role in axon retraction and regeneration. Microarray and RNA-seq studies on cultured mammalian embryonic or early postnatal peripheral neurons showed that axon growth cones contain hundreds to thousands of mRNAs. In the lamprey, identified reticulospinal neurons vary in the probability that their axons will regenerate after axotomy. The bad regenerators undergo early severe axon retraction and very delayed apoptosis. We micro-aspirated axoplasms from 10 growing, 9 static and 5 retracting axon tips of spinal cord transected lampreys and performed single-cell RNA-seq, analyzing the results bioinformatically. Genes were identified that were upregulated selectively in growing (n = 38), static (20) or retracting tips (18). Among them, map3k2, csnk1e and gtf2h were expressed in growing tips, mapk8(1) was expressed in static tips and prkcq was expressed in retracting tips. Venn diagrams revealed more than 40 components of MAPK signaling pathways, including jnk and p38 isoforms, which were differentially distributed in growing, static and/or retracting tips. Real-time q-PCR and immunohistochemistry verified the colocalization of map3k2 and csnk1e in growing axon tips. Thus, differentially regulated MAPK and circadian rhythm signaling pathways may be involved in activating either programs for axon regeneration or axon retraction and apoptosis.